The Application of Regulatory Cascades in Streptomyces: Yield Enhancement and Metabolite Mining - Xia, Haiyang; Li, Xiaofang; Li, Zhangqun; Zhan, Xinqiao; Mao, Xuming; Li, Yongquan (Frontiers in Microbiology, 2020)
Streptomyces is taken as an important resource for producing the most abundant antibiotics and other bio-active natural products, which have been widely used in pharmaceutical and agricultural areas. Usually they are biosynthesized through secondary metabolic pathways encoded by cluster situated genes. And these gene clusters are stringently regulated by interweaved transcriptional regulatory cascades. In the past decades, great advances have been made to elucidate the regulatory mechanisms involved in antibiotic production in Streptomyces. In this review, we summarized the recent advances on the regulatory cascades of antibiotic production in Streptomyces from the following four levels: the signals triggering the biosynthesis, the global regulators, the pathway-specific regulators and the feedback regulation. The production of antibiotic can be largely enhanced by rewiring the regulatory networks, such as overexpression of positive regulators, inactivation of repressors, fine-tuning of the feedback and ribosomal engineering in Streptomyces. The enormous amount of genomic sequencing data implies that the Streptomyces has potential to produce much more antibiotics for the great diversities and wide distributions of biosynthetic gene clusters in Streptomyces genomes. Most of these gene clusters are defined cryptic for unknown or undetectable natural products. In the synthetic biology era, activation of the cryptic gene clusters has been successfully achieved by manipulation of the regulatory genes. Chemical elicitors, rewiring regulatory gene and ribosomal engineering have been employed to crack the potential of cryptic gene clusters. These have been proposed as the most promising strategy to discover new antibiotics. For the complex of regulatory network in Streptomyces, we proposed that the discovery of new antibiotics and the optimization of industrial strains would be greatly promoted by further understanding the regulatory mechanism of antibiotic production.